1976
DOI: 10.1126/science.128820
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stretching Stimulates Synthesis of Matrix Components by Arterial Smooth Muscle Cells in Vitro

Abstract: Rabbit aortic medial cells were grown on purified elastin membranes, which were then subjected to repeated elongation and relaxation or to agitation without stretching. Cells remained attached to the membranes, and cyclic stretching resulted in a two- to fourfold increase in rates of collagen, hyaluronate, and chondroitin 6-sulfate synthesis over those in agitated or stationary preparations. Synthesis of types I and III collagen was increased to the same degree. Stretching did not increase rates of chondroitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(191 citation statements)
references
References 13 publications
6
182
1
2
Order By: Relevance
“…Agerelated arterial remodeling is primarily an adaptive response of the arterial wall to progressive elevations in chronic arterial BP 30) . The results of animal and human studies indicated that an increase in distending pressure is a major stimulus for hypertrophy of smooth muscle cells and the synthesis of extracellular matrix in the arterial wall [31][32][33][34] . Repeated intense cyclic stress may cause fracture of the load-bearing elastin fibers and thus dilation of the lumen 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Agerelated arterial remodeling is primarily an adaptive response of the arterial wall to progressive elevations in chronic arterial BP 30) . The results of animal and human studies indicated that an increase in distending pressure is a major stimulus for hypertrophy of smooth muscle cells and the synthesis of extracellular matrix in the arterial wall [31][32][33][34] . Repeated intense cyclic stress may cause fracture of the load-bearing elastin fibers and thus dilation of the lumen 11) .…”
Section: Discussionmentioning
confidence: 99%
“…That the blebs were characterized by a decreased procollagen expression and decreased elastin content as compared with the adjacent AAA wall 68 again gives rise to the possibility that increased mechanical forces alter local ECM synthesis. This possibility is strengthened by findings that mechanical forces alter ECM production by smooth muscle cells (SMCs), 69 endothelial cells, 70 and other cells 71 in culture. Mechanical forces may also act to alter ECM synthesis in an indirect manner by stimulating cellular release of cytokines such as tumor necrosis factor-␣, 72 which inhibits procollagen expression in human aortic SMCs.…”
Section: Stress-mediated or Strain-mediated Wall Weakeningmentioning
confidence: 98%
“…Both mechanical stimuli and biochemical signals regulate the interaction between the ECM and vascular cells Mack 2011;Humphrey et al 2015). Changes in the ECM are sensed by vascular cells through matrix-binding receptors, such as integrins, and influence cell migration, proliferation, and survival (Moiseeva 2001); in turn, vascular cells can modify the composition and structure of the ECM by increasing or decreasing secretion of matrix proteins and matrix-remodeling enzymes (Leung et al 1976;O'Callaghan and Williams 2000).…”
Section: Structure Of the Arterial Vessel Wallmentioning
confidence: 99%